2010
DOI: 10.3748/wjg.v16.i20.2531
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease andHFEgene mutations: A Polish study

Abstract: HFE mutations conferred no additional hepatic fibrosis risk in NAFLD, but higher serum iron was a risk factor for severe liver damage in NAFLD, regardless of HFE mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
2
13
2
Order By: Relevance
“…Although NASH was initially described as a disease predominantly affecting women [11], there are still controversies on this matter. Recently, we evaluated the HFE gene mutation in Caucasians with NAFLD, and multivariate logistic regression analysis showed female gender as a risk factor for more advanced fibrosis [12]. Also, in the present study, females were predominant in the F3-F4 subgroup, showing a trend by the Fisher test (p = 0.08).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although NASH was initially described as a disease predominantly affecting women [11], there are still controversies on this matter. Recently, we evaluated the HFE gene mutation in Caucasians with NAFLD, and multivariate logistic regression analysis showed female gender as a risk factor for more advanced fibrosis [12]. Also, in the present study, females were predominant in the F3-F4 subgroup, showing a trend by the Fisher test (p = 0.08).…”
Section: Discussionsupporting
confidence: 63%
“…In a Polish cohort, we recently found the highest serum ferritin levels in a subgroup of NASH patients with F3-F4 fibrosis; however, it was without statistical significance and higher levels of serum iron, as well as DMt2, were associated with severe liver fibrosis [12]. There is growing evidence that iron and glucose metabolism are interdependent and that increased iron stores may contribute to insulin resistance (IR).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study we found that male gender was associated with a lower level of severe fibrosis in the Polish NAFLD group [10]. It seems to be more interesting, although it is not certain, whether the higher activity of sPLA 2 observed in women was the result of more advanced age and dyslipidemia.…”
Section: Discussionmentioning
confidence: 88%
“…136,137 Mutation to the HFE gene dysregulates iron absorption, resulting in increased extracellular iron. 138,139 Increased extracellular iron alters the microbiome within the GIT.…”
Section: Study 2 (Chapter 4)mentioning
confidence: 99%
“…136,137 This mutation disrupts iron absorption, resulting in increased extracellular iron. 138,139 Iron is an essential element for all bacteria, with a few exceptions such as B. burgdorferi 140 (implicated in Lyme disease), and some lactic acid bacteria. 141 Elevated levels of extracellular iron may result in increased gastrointestinal tract pathogen toxicity 142 resulting in increased intestinal permeability and inflammation.…”
Section: Introductionmentioning
confidence: 99%